Hubungan Tata Ibadah Remaja Terhadap Pertumbuhan Iman di Gereja Kristen Oikumene (GKO) Pematang Tembesu Jambi - Kevin Halomoan Hutagalung; Elisamark sitopu; Meditatio Situmorang; Ibelala Gea; Megawati Manullang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the relationship between youth worship systems and faith growth in GKO Pematang Tembesu and to explain how youth worship systems can increase youth faith in GKO. This study is based on the youth worship system carried out by the church, it can be seen that faith is not growing well in adolescents, as seen from poor behavior and lack of responsiveness in following every worship service carried out by GKO. Of course, this is something that really needs to be considered in order to create a strong and God-fearing youth faith. In this study, the researcher used a descriptive inferential method with a quantitative approach, the data obtained through observation, interviews, questionnaires (questionnaires) and documentation. Data is obtained and data processing is carried out in order to obtain the desired results. The population of this study was all GKO adolescents totaling 30 people. This study was carried out by the author at the Oikumene Christian Church, Pematang Tembesu, Jambi and was carried out from November 2023 to January 2024.The results of the questionnaire from the respondents were processed and compiled and tabulated in a table according to the items submitted. To find out the Pearson Product Moment, the rxy value is obtained = 0.666. And with r table 0.308308, it can be said that there is a positive and significant relationship between worship order and faith growth in GKO Pematang Tembesu. With a significant p = 0.000 <0.050, the hypothesis of the study is that there is a positive relationship between worship order and faith growth. This means that based on the research, the hypothesis in this study is accepted. The determinant coefficient (r2) of the relationship between variable x and variable y is r2 = 0.443, this shows that worship order is related to faith growth by 44.3%.